Helicobacter pylori Isolation and Antibiotic Susceptibility Testing Using Rapidly Frozen Biopsy Samples - Kee Don Choi; Jung Mogg Kim; Gwang Ho Baik; Jun Chul Park; Hye-Kyung Jung; Han Seung Ryu; Soo-Jeong Cho; Cheol Min Shin; Hwoon-Yong Jung; Korean College of Helicobacter and Upper Gastrointestinal Research (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2024)
Objectives To involve institutions without the ability to perform susceptibility testing, long-term storage of tissue sample is critical to isolate the bacteria in a central laboratory. The aim of the study was to investigate the feasibility of H. pylori isolation and antibiotic susceptibility testing using rapidly frozen biopsy specimens collected from various institutions. Methods Eight institutions located in various regions of Korea participated in the study. Patients requiring upper endoscopy and H. pylori testing were screened. Two biopsy samples were taken from the stomach. One was placed in a sterile Eppendorf tube and then immediately placed in a vacuum bottle containing dry ice, which was stored at -80°C. The other was used in a rapid urease test. Collected samples were delivered to a central laboratory. The bacteria were isolated from the frozen samples under microaerophilic conditions. The agar dilution method was used to determine the minimum inhibitory concentration (MIC) of amoxicillin, clarithromycin, metronidazole, tetracycline, ciprofloxacin, and levofloxacin for each H. pylori isolate. Results Patients with a positive rapid urease test result (n=113) were enrolled. The mean age was 56.6±12.3 years. The male:female ratio was 64:49. The overall culture success rate was 77.0% (87/113). MIC values were determined using isolated 87 H. pylori strains. Rates of resistance to amoxicillin, clarithromycin, metronidazole, tetracycline, levofloxacin, and ciprofloxacin were 23.0%, 25.3%, 28.7%, 1.1%, 33.3%, and 34.5%, respectively. Conclusions It is feasible to perform H. pylori isolation and antimicrobial susceptibility testing using rapidly frozen and transported biopsy specimens.